Frontal mucocele: Surgical approach? Two cases report - Peixoto, Conceição (2013)
Introduction: Frontal mucoceles are benign lesions, but can invade adjacent structures such as the orbit. The need for surgical treatment in this pathologyis unquestionable. However the same is not true regarding the best technique to follow. Endoscopic or external approach? Marsupialization or complete excision? These are some of the issues still under debate.Cases Report: Two cases of unilateral fronto-ethmoid mucoceles are presented. Two male patients, aged over 70 years, without complaints of nasal pathology, presenting with proptosis and visual changes. They underwent an external and combined approach, including nasofrontal endoscopic and external approach with re-permeabilization of the nasofrontal duct.Discussion: The choice of technique and surgical approach depends on the surgeon’s experience, the extent and location of the lesion and patient choice. The excision of the lesion by a combined approach may be considered in this pathology.